Na’matakning biologik xususiyati va tibbiyotdagi ahamiyati - Rustamova Iqboloy Akramjon qizi; Ruziyeva Gulsara Temirqulovna (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
This article describes in detail the role of the dog rose (Rosa canina L.) plant in human health, its biological, pharmacological, nutritional, prophylactic and therapeutic properties. The chemical composition of dog rose, its ancient uses in folk medicine, clinical studies in modern medicine, its effect on immunity, beneficial aspects in the cardiovascular system, gastrointestinal function, skin and endocrine systems are described on a broad scientific basis. The nutritional value of the plant, its bioactive substances, and its therapeutic potential in the form of dried fruits and tinctures are also analyzed in depth. At the end of the article, a general conclusion about the importance of dog rose and the literature used are presented.